232 EPNS4Surge: an MDT-designed integrated learning course facilitating effective patient flow from triage to discharge. (17th August 2022) - Hughes, Ben; Mathai, Mathew
Abstract : Aims: Nurses are experienced at identifying and managing unwell children. The Enhanced Paediatric Nursing Skills for Surge (EPNS4Surge) course builds on this by providing specific training to enable the development of urgent care paediatric services. This includes enhanced nurse triage, nurse-led discharge, and hospital at home (H@H) community care. EPNS4Surge was inspired and developed by a MDT of nurses, nurse practitioners, paediatricians and primary care clinicians to provide high-quality urgent care for sick children. Course Aims: Enable personal and professional paediatric nursing development Facilitate development of innovative workflows Improve patient flow during surges in activity for children with respiratory presentations Build close working relationships between primary, secondary and community paediatric care Methods: This EPNS4Surge course is freely available to those working in the NHS. It is flexible in timescale for completion, with the option of tailoring teaching components according to available resources and local requirements. The course combines online learning with local supervised placement-based training. It focusses on asthma, viral-induced wheeze, croup and bronchiolitis, as well as spotting the sick child and effective handover. Following a supervised placement-period, a summative OSCE and competency assessment are completed in the students own place of work. A Quality Improvement approach is encouraged to assess service needs pre and post intervention. Results: EPNS4Surge has been developed using the governance processes and clinical workflows utilised by the Bradford H@H model. Their bronchiolitis home-oxygen pathway alone has facilitated early discharge for 5 babies over 3 months, saving 12 bed-days. We anticipate similar results can be achieved through EPNS4Surge, however the long-term benefits will only be demonstrable after completion of the course and implementation of novel workflows. Qualitative data will also be collected to explore how individuals and teams have used the course to enhance self-development and service-development. Successful students may use this learning opportunity as a step towards completing the full EPNS course. This Masters-level 30-credit module is run twice a year at the University of Bradford. Conclusion: EPNS4Surge is a freely available course developed for local implementation and encourages teams to invest in nurse training to address the increasing demand and pressures on acute paediatric services.